1999
DOI: 10.4269/ajtmh.1999.60.430
|View full text |Cite
|
Sign up to set email alerts
|

Potential for evolution of California serogroup bunyaviruses by genome reassortment in Aedes albopictus.

Abstract: Abstract. Aedes albopictus was introduced into the United States in used tires in 1985. Its successful colonization of the upper Midwest has potential to alter the current epidemiology of bunyaviruses that circulate in the region. It is permissive for the replication of several arboviruses, including La Crosse (LACV) and Jamestown Canyon (JCV) bunyaviruses. In this study, we demonstrate the ability of LACV and JCV to coinfect Ae. albopictus mosquitoes and to form all six possible reassortant genotypes. All rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The impact of diseases on formerly naṏve human and wildlife populations due to introduced mosquitoes is well-documented (Morgan 1981, Bryan 1999. Furthermore, newly established associations between vectors and local parasites may result in deadly combinations (Cheng et al 1999). There is, therefore, the potential for major disease epidemics fueled by newly established associations of parasites, hosts, and vectors.…”
mentioning
confidence: 99%
“…The impact of diseases on formerly naṏve human and wildlife populations due to introduced mosquitoes is well-documented (Morgan 1981, Bryan 1999. Furthermore, newly established associations between vectors and local parasites may result in deadly combinations (Cheng et al 1999). There is, therefore, the potential for major disease epidemics fueled by newly established associations of parasites, hosts, and vectors.…”
mentioning
confidence: 99%
“…Segment 2 of Chuzan virus encodes the outer capsid protein VP2. Reassortment of genome segments can contribute to virus diversity and is known to occur in orbiviruses [25]; the distinct relationship of segment 2 may be the result of reassortment. The RNA segment name, encoded protein as well as putative function were assigned according to the nomenclature of the Orbivirus type species BTV (Table 4) following recommended rules [23].…”
Section: Resultsmentioning
confidence: 99%
“…Second, JCV produces viremia in monkeys and is neurovirulent in mice, providing two animal models to evaluate the level of attenuation and efficacy of a recombinant chimeric JCV/LACV if it were obtained. Third, although JCV and LACV reassortants have not been identified in nature, previous research indicated that a reassortant iso- lated from dually infected mosquitoes and containing the fulllength M segment from JCV in a LACV background was viable, with neuroinvasiveness and neurovirulence phenotypes like those of its JCV parent virus (9). This indicated that the JCV G N , NS M , and G C proteins were compatible with the L, N, and NS S proteins of LACV, thus increasing the likelihood that the desired rJCV/ LACV antigenic chimeric virus could be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Chimerization did not affect virus growth in tissue culture, and rJCV/LACV maintained the robust growth kinetics observed for the parental viruses. The absence of in vitro growth restriction following chimerization was not surprising, since the reassortant virus that contained the full-length M segment from JCV in a LACV background exhibited virulence similar to that of its JCV parent in mice (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation